Figurative Language in “Cross Road” Album by Bon Jovi: Semantics Analysis - Ismidiani, Adinda; Deden Novan Setiawan Nugraha (International Journal of English Linguistics, Literature, and Education (IJELLE), 2025)
This journal examines the important relationship between culture and language, emphasizing the role of both in human communication. Language serves as the primary means of expressing emotions and sharing information, while culture shapes the way we use language in complex ways. This research focuses on figurative language in song lyrics, particularly from Bon Jovi's “Cross Road” album, to uncover deeper meanings and evoke emotions. This research aims to analyze the types of figurative language present in the songs and the meaning conveyed through the lyrics. Using a qualitative method, this study collected and evaluated data based on Perrine's classification of figurative language, which includes twelve types; however, this study focuses on six types: simile, metaphor, personification, symbol, hyperbole, and irony. The findings of this study reveal 79 instances of figurative language throughout the album, with the following distribution: personification (12 items or 15%), metaphor (19 items or 24%), hyperbole (14 items or 17%), simile (7 items or 8%), irony (9 items or 11%), and symbol (18 items or 22%). It can be said that the dominant type of figurative language in this album is metaphor.